Тенденції розвитку сонячної і вітрової енергії - Соркіна, Діана Костянтинівна; Тихомирова, Тетяна Сергіївна (ФОП Яроченко Я. В., 2024)
Alternative energy sources are at the forefront of resource efficiency in the enterprise. The steady rise in natural resource prices, awareness of the benefits of a «green» economy, and the fight against climate change are forcing governments in many developed countries to develop new legislative initiatives at both the national and international levels. Oil, gas, and coal are exhaustible fossil fuels, so alternative energy sources should be sought. Therefore, we should consider such energy sources as wind and solar.
Keywords: сонячна енергія; вітрова енергія; джерела енергії; вітроенергетика; електроенергія; електростанції